Docetaxel rechallenge in metastatic castration-resistant prostate cancer: any place in the modern treatment scenario? An intention to treat evaluation. (November 2015) - Bracarda, Sergio; Caserta, Claudia; Galli, Luca; Carlini, Paolo; Pastina, Ilaria; Sisani, Michele; Scali, Simona; Hamzaj, Alketa; Derosa, Lisa; Felici, Alessandra; Rossi, Marta; Altavilla, Amelia; et al.
Background: We evaluated the possible advantages of a docetaxel (DCT) rechallenge strategy in metastatic castration-resistant prostate cancer (mCRPC) patients, also given the possible earlier positioning of this treatment option in the modern scenario.Patients & methods: All mCRPC patients planned for DCT chemotherapy rechallenge in our institutions were evaluated.Results: Of 128 patients, 98 achieved disease control on the initial DCT round. After a treatment holiday of 8.3 months, the 98 responsive patients underwent a second DCT round, with 56 cases achieving again disease control. After a 5.7-month off-treatment period, 32 of these cases underwent a third DCT round, and 16 responded. Lastly, after a further 4.2-month treatment holiday, eight patients underwent a fourth DCT round and two responded. Median time to definitive disease progression for the whole population was 16.4 months.Conclusions: Rechallenge with DCT may be considered a suitable treatment option for mCRPC patients recurring after a successful DCT chemotherapy. The interest in this strategy may be increased because of the showed efficacy of early DCT chemotherapy in patients with bulky disease (CHAARTED study) and the potential lower efficacy of the new hormonal agents abiraterone acetate and enzalutamide when used in a immediate sequencing.